Impact of the COVID-19 Pandemic on Household Welfare, Food Security, and Agriculture in Central Asia - Akramov, Kamiljon T. (2020)
Kamiljon Akramov and Katrina Kosec POLICY SEMINAR Virtual Event - Food Policy Research and Capacity Development in Eurasia Co-Organized by the Eurasian Center for Food Security (ECFS), World Bank Group, and IFPRI DEC 2, 2020 - 07:30 AM TO 09:00 AM EST